Association of the availability of pharmaceutical facilities provided in secondary and tertiary hospitals with clinical pharmacists' work performance - Rong Cai; Xiaoyu Xi; Yuankai Huang (BMC, 2023)
Abstract Background Clinical pharmacists always work as the pivotal role in the process of facilitating the proper use of drug. Based on the person-environment fit theory, the availability of facilities required in pharmaceutical service may influence pharmacists' performance, but which of them may have positive or negative impact remains unclear. Objectives This study aims to analysed the quantitative association of the availability of pharmaceutical facilities provided in Chinese hospitals and clinical pharmacists' work performance to assist hospitals formulating plans of the improving pharmaceutical working conditions to enhance clinical pharmacists' performance. Method Demonstrated by the panel of expert and literature review, the questionnaire for administrators and clinical pharmacists of secondary and tertiary hospitals in China was formed. Then a mixed sampling was adopted to gather data on information of the participants, as well as evaluation indexes of the availability of facilities and clinical pharmacists' work performance. Results Overall, 625 questionnaires distributed to administrators of hospitals and 1219 ones distributed to clinical pharmacists were retrieved. As for the Pharmaceutical facilities, while the increased availability of Traditional Chinese medicine pharmacy (p = 0.02) has a significantly positive impact on clinical pharmacists' performance, the great availability of the preparation room (p = 0.07) negatively influences their work performance. Conclusion Improving the availability of facilities that significantly influence clinical pharmacists' work performance possibly reduce their workload, enhance their efficiency and further promote progress in pharmaceutical service.